MEASUREMENT OF FUNDAMENTAL ILLITE PARTICLE THICKNESSES BY X-RAY DIFFRACTION USING PVP-10 INTERCALATION - Eberl D.D.; Nüesch R.; Sucha V.; Tsipursky S. (My University, 1998)
The thicknesses of fundamental illite particles that compose mixed-layer illite-smectite (I-S) crystals can be measured by X-ray diffraction (XRD) peak broadening techniques (Bertaut-Warren- Averbach (BWA) method and integral peak-width method) if the effects of swelling and XRD background noise are eliminated from XRD patterns of the clays. Swelling is eliminated by intercalating Na-saturated I-S with polyvinylpyrrolidone having a molecular weight of 10,000 (PVP-10). Background is minimized by using polished metallic silicon wafers cut perpendicular to (100) as a substrate for XRD specimens, and by using a single-crystal monochromator. XRD measurements of PVP-intercalated diagenetic, hydro- thermal and low-grade metamorphic I-S indicate that there are at least 2 types of crystallite thickness distribution shapes for illite fundamental particles, lognormal and asymptotic; that measurements of mean fundamental illite particle thicknesses made by various techniques (Bertant-Warren-Averbach, integral peak width, fixed cation content, and transmission electron microscopy (TEM)) give comparable results: and that strain (small differences in layer thicknesses) generally has a Gaussian distribution in the log- normal-type illites, but is often absent in the asymptotic-type illites.